Utilization of jackfruit or langka 9arthocarpus integra L) and tiessa (lucuma nervosa) seeds flour in the preparation of snack items (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2001)
This study was conducted to determine the possibility of replacing some amount of the wheat flour used in the preparation of snack item such as doughnut, and polvoron. The indigenous source of wheat flour replacement were langka and tiessa seeds. The proportion of wheat flour replaced in the preparation of snack items constitute the treatments evaluated. These includes 0% replacement or 100%-0% wheat flour- indigenous flour mixture (T1), 25% replacement or 75%-25% mixture (T2), and 50% replacement or 50%-50% mixture (T3), and 75% or 25%-75% mixture (T4). A panel of experienced food tasters evaluated the products based on appearance, texture, and flavor using the Hedonic Scale. Using ten evaluators as replication, the Completely Randomized Design (CRD) was used to analyze the qualities of snack items. Results of the study revealed that tiessa seeds had a flour yield of 54.8% while langka seeds had 51.6%. Comparable appearance was observed in doughnut from indigenous flour (langka seed and tiessa seed) and wheat flour mixture. The texture in terms of tenderness and flavor of doughnuts from 50% wheat flour and 50% langka seeds were as desirable as the doughnut from pure wheat flour (control). The appearance, tenderness, and flavor of doughnuts was not significantly affected with the replacement of wheat flour with tiessa seed flour. The substitution of langka seed and or tiessa seed flour combination significantly changed the appearance of the polvoron. The degree of desirability of flavor in polvoron increases in tiessa seed flour-wheat flour combinations. Considering that langka and tiessa seeds are free, the cost and return analysis revealed that doughnut and polvoron made from treatments with the least proportion of wheat flour gave the highest net profit.